2016
DOI: 10.1159/000449278
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Development of the Orexinergic (Hypocretinergic) System in the Central Nervous System of <b><i>Xenopus laevis</i></b>

Abstract: The present immunohistochemical study represents a detailed spatiotemporal analysis of the localization of orexin-immunoreactive (OX-ir) cells and fibers throughout development in the brain of the anuran amphibian Xenopus laevis, a model frequently used in developmental studies. Anurans undergo remarkable physiological changes during the early life stages, and very little is known about the ontogeny and the localization of the centers that control functions such as appetite and feed ingestion in the developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 106 publications
(145 reference statements)
2
5
0
Order By: Relevance
“…These results follow previous studies conducted by our group in cladistian fishes, lungfishes, amphibians, and reptiles [López et al, 2009a[López et al, , 2009b[López et al, , 2016Domínguez et al, 2010]. The specificity of the antibodies was confirmed with control series, suggesting that the substances recognized are only orexins, although the presence of orexins in holostean fishes remains unknown.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These results follow previous studies conducted by our group in cladistian fishes, lungfishes, amphibians, and reptiles [López et al, 2009a[López et al, , 2009b[López et al, , 2016Domínguez et al, 2010]. The specificity of the antibodies was confirmed with control series, suggesting that the substances recognized are only orexins, although the presence of orexins in holostean fishes remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it has been demonstrated that the synthetic human OXA has physiological activity in teleosts [Volkoff et al, 1999[Volkoff et al, , 2003Volkoff and Peter, 2001;Nakamachi et al, 2006;Yokogawa et al, 2007], which indicates that, despite the changes in the structure of orexins in vertebrates, there is still a high similarity between orexins in teleosts and humans. The anti-OXA and anti-OXB antisera used in this study were raised against a peptide mapping at the C-terminus of human OXA or OXA, whose invariability, together with the fact that orexins do not have structural homology with other biologically active peptides [Shibahara et al, 1999], accounts for the consistency in the immunolabeling pattern obtained with both antibodies in this and previous studies [Singletary et al, 2005[Singletary et al, , 2006López et al, 2009aLópez et al, , 2009bLópez et al, , 2014López et al, , 2016Domínguez et al, 2010;Miranda et al, 2013].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations